Strategies to Optimize Strength and Endurance Concurrent Training in Elite Handball - Sergio Sánchez López; Manuel A. Rodríguez Pérez (Federación Extremeña de Balonmano; University of Extremadura, 2017)
Aim: To review the existing literature about concurrent strength and endurance training for elite handball players in order to determine valid strategies to plan training programs. Methodology: The literature in databases such as PubMed, SpringerLink, etc. was systematically reviewed following the guidelines established in the PRISMA guide by Urrutia & Bonfill (2010), using the performance of elite athletes-who were the research subjects-as exclusion criterion. Results and Discussion: The results showed the need to control the combination of different intensities when training both capacities, the frequency of the sessions, and the order and minimum recuperation that must exist when two sessions of both capacities are scheduled on the same day. Conclusions: The study revealed that when combining different intensities with the objective of avoiding the interference phenomenon, the intensities used should not be those that could produce peripheral adaptations, and that an 8-hour interval must be left in case of having two sessions on the same day. Furthermore, it became clear that players with more strength and power might have a head start in the game actions due to the strength requirements of the sport.